Meningkatkan Kemampuan Sosial Peserta Didik Melalui Program Kooperatif di SDN 2 Karangtengah - Wulandari, Desi; Khoerrunisa , Rizkia Amanda; Pramesthy, Siska Dwi; Nurkholis (Innovative: Journal Of Social Science Research, 2025)
Students' social skills are a crucial component in shaping their character and supporting their academic success. This article presents a systematic review of the role of cooperative learning in developing students' social skills. Combining theoretical approaches and empirical findings, this article reviews various models of cooperative learning implementation that have proven effective, along with potential challenges and strategies for overcoming them. This article is based on modern educational theory and supported by relevant research data.